Perancangan Dan Aplikasi Pembangkit Plasma Tegangan Tinggi AC Menggunakan Dual Flyback Transformator (TFB) Topology Inverter Half Bridge - Muhammad Rafi Epafras; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The implementations of high voltage electricity in various fields, one of it leads to eco friendly technology known as plasma technology. The use of plasma technology is utilized in the production process of advanced nano-sized materials. Plasma can be generated by the corona discharge method which is generally used as a method of generating plasma supplied with highvoltage or also known as high voltage plasma generators. The limitation of high voltage generation becomes a barrier in generating high voltage plasma, because the high voltage generator exist is still in a large scale. So, it needs a high voltage plasma generator in a laboratory-scale. In this research, high voltage plasma generators will be designed using two flybacktransformers with half-bridge inverter using MOSFET as switching devices. Switch is controlled by the control circuit IC 4047CDwith a frequency of 33 kHz at a duty cycle of 50%. The comparison of coils on the flyback transformer used is 1:75. The resulting plasma will be applied in producing a layer of graphene from coconut shell carbon waste. Plasma is raised with rod electrodes and plate electrodes. The test carried out with variations in inverter h-bridge input voltage.. For Variations in inverter inputvoltage used are 10, 12.5, 15 and 17,5 V. The test results showed that variations in inverter h-bridge input voltage could affect theamount of plasma produced, and plasma also affects the yield of decomposed carbon materials with high voltage plasma produced 1,40 kV and 2,57 kV at a distance between electrodes 5 mm.Keywords : Flyback Transformers, Half Bridge, Plasma, Graphene.